A Case of Tumor of Follicular Infundibulum Involving the Vulva - Victor Santiago; David Cartwright; Pooria Khoshnoodi; Molly Klein; Alessio Giubellino (Case Reports in Pathology)
Tumor of the follicular infundibulum or infundibuloma is a relatively rare benign adnexal tumor usually solitary and located in the head, neck, and trunk. Here we present a 70-year-old woman with a tender vulvar lesion. Histopathologic exam shows a well-circumscribed lesion with a subepidermal horizontally oriented, plate-like proliferation of pale appearing squamous epithelial cells with numerous points of connections with the overlying epidermis and peripheral palisading. Overall these histopathologic features are consistent with the diagnosis of tumor of follicular infundibulum involving genital skin.